sage: alpha=sqrt(-11/2 + sqrt(11^2-4(11))/2) sage: alpha=sqrt(-11/2 - sqrt(11^2-4(11))/2) sage: K=QQ[alpha,beta]

1 | initial version |

sage: alpha=sqrt(-11/2 + sqrt(11^2-4(11))/2) sage: alpha=sqrt(-11/2 - sqrt(11^2-4(11))/2) sage: K=QQ[alpha,beta]

sage: alpha=sqrt(-11/2 + sqrt(11^2-4(11))/2) sage: alpha=sqrt(-11/2 - sqrt(11^2-4(11))/2) sage: K=QQ[alpha,beta]

I tried:

```
sage: alpha=sqrt(-11/2 + sqrt(11^2-4(11))/2)
```~~ ~~sage: alpha=sqrt(-11/2 - sqrt(11^2-4(11))/2)
~~ ~~sage: ~~K=QQ[alpha,beta]~~K=QQ[alpha,beta]

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.